Perceptions of UPIS High School students batch '98 on library and information science as a profession - Bihis, Arthur P.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
This study is entitled "Perceptions of UPIS (University of the Philippines Integrated School) High School Batch '98 on Library and Information Science as a Profession." The study aims to find out what these students know about library and information science as a profession and the factors that influenced their ideas. Forty-five respondents out of 260 students in the batch were used as samples. There are 30 females and 11 males. Their ages ranges from 15-17 years old.
A questionnaire was used as instrument for data gathering. It is divided into four parts: 1) respondents profile; 2) family background; 3) awareness on library and information science as a profession and; 4) choice of profession field.
The study found out that majority of the respondents does not have any ideas or insights on Library and Information Science as a profession. Of those who had ideas and insights on the profession, they indicated selection and acquisition of books and other information materials, caring of the library and its contents, book filing, book arranging, book evaluation, information processing and handling and software applications and providing book loan services as part of the profession's line of work. They were able to get their knowledge of the profession from school, family and media.
There were 28 respondents who did not want to pursue the profession. Their reasons are: 1) the course is boring; 2) hard; 3) does not pay well; 4) uninteresting; 5) offers only clerical work and; 6) the course is just all about reading books and other related tasks. Out of the 45 respondents, 13 indicated that they are interested in pursuing Library and Information Science as a profession. Of the 13 who said yes, only three indicated their reason is that the profession offers a big salary.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: High school students -- Quezon City. -- Philippines; Information science; LIbrary science